Visual object classification from fMRI data - Newaz, Syed Mishar; Taseeb, Taslim Ahmed; Haque, Abdullah Nurul (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.